The great cake mystery [compact disc, unabridged] : Precious Ramotswe's very first case - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2012)
Before becoming the first female private investigator in Botswana, eight-year-old Precious Ramotswe tracks down a thief who has been stealing her classmates' snacks.